Quantification of variation in dose–volume parameters for the heart, pericardium and left ventricular myocardium during thoracic tumor radiotherapy. (5th April 2018) - Tong, Ying; Yin, Yong; Cheng, Pinjing; Lu, Jie; Liu, Tonghai; Chen, Jinhu; Gong, Guanzhong
Abstract: Cardiac activity can induce dose–volume evaluation errors for cardiac structures. The purpose of this study was to quantify the variation in dose–volume parameters for the heart, pericardium and left ventricular myocardium (LVM) throughout the cardiac circle. The heart, pericardium and LVM of 22 patients were contoured on 20 phases of electrocardiography-gated 4D computed tomography (4DCT) images acquired during breath-hold. Radiotherapy plans were designed on 0% phase of the 4DCT images, and the dose distributions of the plans were imported into MIM Maestro and deformed to each phase to generate distributions for all phases. Variations in dose–volume parameters for the heart, pericardium and LVM were compared among different phases. The rates of variation in Dmean for the heart and pericardium were 3.33 ± 1.04% and 2.66 ± 1.15%, respectively. The mean values of the maximum difference in V5, V10, V20, V30 and V40 were all <2% for the heart and pericardium and were not statistically significant ( P > 0.05). The rate of variation in Dmean for the LVM reached 87.05 ± 38.34%, and the maximum differences in V5, V10, V20, V30 and V40 were 13.76 ± 4.46%, 13.64 ± 4.33%, 12.84 ± 4.55%, 11.62 ± 4.85% and 3.63 ± 2.56%, respectively; all differences were statistically significant ( P < 0.05). Variations in dose–volume parameters were more significant in the LVM than in the heart and pericardium ( P < 0.05). The dose–volume parameters for the LVM were significantly influenced by cardiac activity, whereas those for the heart and pericardium were not; therefore, individual dosimetric evaluation and limitation must be performed for the LVM.